정상인과 폐쇄성 및 제한성 폐질환 환자에서 폐탄성에 대한 연구 - 이홍렬; Hong Lyeol Lee; 김성규; Sung Kyu Kim; 이원영; Won Young Lee (The Korean journal of medicine, 1993)
Background: Lung distensibility or elastic recoil is generally evaluated by lung compliance which is defined as the ratio of the change in lung volume to a change in transpulmonary pressure in the absence of airflow, that is to say, the slope of the pressure-volume curve (P-V curve). Pulmonary compliance is usually of more clinical interest than chest wall compliance because the majority of diseases affect the lungs rather than chest wall. Pulmonary compliance is not constant over the entire range of vital capacity and plotting P-V relationships results in a curve rather than a straight line. But if it is taken at a particular volume range, conventionally from functional residual capacity (FRC) to (FRC+0.5L), the curve becomes almost nearly linear with consistent and reproducible slope and because of the absence of a forced expiration, airway and extrapulmonary factors are not involved. Dynamic compliance is reduced not only by stiffening of the lung parenchyme but also by relatively minor changes in the airways, and therefore, it is a reliable measure of the peripheral airway disease rather than lung elasticity. Methods: Subjects were divided into four groups; normal control groups below 35 years old and above 50 years old, and patient groups of obstructive and restrictive pulmonary diseases. We did this study in sequence of arterial blood gas measurement, flow-volume curve, body plethysmography, diffusion capacity and measurement of lung compliance. Esophageal balloon volumes were restricted to less than 0.5 cc and location was confined to the lower 1/3 of the esophagus. We measured the dynamic compliance about 10 times during the tidal breathing. After then, to obtain the static expiratory P-V curves, the subjects performed a sequence of full inflation up to the level of total lung capacity (TLC), where the breath should be held for two or three seconds at TLC to obtain a near-pleteau of pressure. The subsequent expiration was then interrupted by obstruction at the mouthpiece after successive small decrements of volume with 1-2 seconds pause at each volume. As a result of making the above examination about five times, we obtained the average values of static lung compliance. Specific compliance, maximal static recoil pressure, and coefficient of retraction were also calculated. Results: Static compliance was significantly reduced in patient groups of obstructive lung diseases other than emphysema and restrictive lung diseases. Specific compliance also showed similar results. Maximal static recoil pressure showed characteristic findings such as the reduction in extrapulmonary restrictions and elevation in parenchymal restrictions. Coefficient of retraction was increased only in the cases of restrictive pulmonary diseases. Results on dynamic compliance by the hypoxia and static compliance by the hypercapnia showed significant differences and specific compliance results showed significant difference both by the hypoxia and hypercapnia, Conclusion: Static compliance and specific compliance were significantly decreased in pulmonary disease groups and they were thought to be useful indexes for lung elasticity. Maximal static recoil pressure was useful for differential diagnosis between parenchymal and extrapulmonary restrictions. Coefficient of retraction was characteristically elevated in restrictive pulmonary diseases and useful in differential diagnosis between restrictive lung diseases and normal or obstructive lung diseases. Dynamic compliance was affected by airway resistance as well as lung volume.